Propuesta de un sistema integrado de gestión para la empresa SGS ETSA fundamentado en los requisitos de la norma NTC-ISO 9001: 008 e ISO 27000 para el contrato No. 0010649 - Montealegre Rodríguez, Diana Carolina; Rojas Diaz, Mileiby; Contreras Quintero, John Fredy (Escuela Colombiana de Ingeniería Julio Garavito, 2013)
The hydrocarbons sector in Colombia has stood out for promoting the economic growth of the country, generating the increase of resources that territorial entities receive for oil and gas production and foreign investment that has been increased by 89% compared to year 2010. Figures that are reflected in a source of income and permanent employment for large companies and multinationals. The SGS Group is the world's largest organization in the fields of Inspection, Verification and Testing. Founded in 1878, it has expanded all over the world, operating in more than 140 countries. The SGS Group is unique, not only because of its geographic coverage, but also because of the range of services it offers. In Colombia it has been operating since 1956 and since 1976, under the corporate name SGS Colombia S.A. and as a direct subsidiary of the Group, it opens offices in Bogotá and the main cities of the country. SGS Colombia S.A. is a global provider of technical verification, inspection, testing and appraisal compliance services, instilling confidence in customers. We ensure that the quality and development of your products or facilities comply with the applicable requirements, whether regulatory, voluntary or customer specifications. The goal is to help improve the integrity, quality and efficiency of equipment, ensure the safety and welfare conditions of workers and minimize the impact of industrial activities. These services are applied in engineering, construction projects, improvement in maintenance activities. Employees in the Industrial Services sector are the best qualified and recognized experts in the industry. We have decades of experience, our work is recognized by numerous accreditations by international organizations as well as standard specifications of our clients. Our experience can help you improve the conditions of your employees in safety and health, and in the impact of your activities. TECHNICAL STUDIES S.A. is an engineering company founded in 1964 with the purpose of providing engineering services to seek, define and implement comprehensive, innovative and economic solutions to the complex problems that development poses to the public and private sectors, inside and outside the country. Since its foundation, it has carried out works in the areas of Design, Intervention, Studies, and Consulting, Basic and Detail Engineering, Project Management and Construction, Industrial Appraisals and Inspection of Manufacturing and Assembly of Equipment throughout the Colombian territory, contributing to the development of the country. Several of his works have been executed in consortium with national firms or in consortium or with advice from foreign firms. A significant number of projects that have been worked on have been financed with loans from entities such as the Inter-American Development Bank (IDB), the International Bank for Reconstruction and Development (IBRD) and the United Nations Development Program (UNDP). SGS ETSA is currently developing several macro contracts with Ecopetrol S.A. that open the doors and position it as a leading company in the market. With the need for expansion and to provide a service that satisfies the expectations of its customers, SGS ETSA requires the implementation of an integrated management system that allows it to obtain optimum performance in its commercial activity, bringing with it economic benefits, the optimization of its resources through efficiency and effectiveness in the exercise of their work. With the expansion of the market it has become necessary to implement methodologies that allow organizations to be more competitive, not only nationally but internationally, being of vital importance the satisfaction of the client in all its aspects. With the implementation of quality systems based on ISO 9001 version 2001, companies take a step forward in the development of administrative systems based on Integral Management, which in the medium and long term results in their survival and growth. SGS ETSA aware of that need has been directed to the achievement of the quality of its products for this specific case it is decided to implement an integral system that adapts to the design for each hydrocarbon project; it is for this reason that it is decided to carry out the design of the integral management system ISO 9001 ISO 27000, taking as an example and field of investigation the Contract No. 0010649 whose object is "Civil, electrical and piping designs for the facilities of the campaign of drilling of the vice presidency of exploration and production validity 2013 ".

El sector de los hidrocarburos en Colombia se ha destacado por promover el crecimiento económico del país, generando el aumento de recursos que reciben los entes territoriales por la producción de petróleo y gas y la inversión extranjera que se ha aumentado en un 89% en comparación al año 2010. Cifras que se reflejan en una fuente de ingresos y empleo permanente para las grandes empresas y multinacionales. El Grupo SGS es la Organización más grande del mundo en los campos de la Inspección, Verificación y Ensayo. Fundado en 1878 se ha expandido por todo el mundo, operando en más de 140 países. El Grupo SGS es único, no sólo por su cubrimiento geográfico, sino también por la gama de Servicios que ofrece. En Colombia opera desde 1956 y a partir de 1976, bajo la razón social SGS Colombia S.A. y como filial directa del Grupo, abre oficinas en Bogotá y las principales ciudades del país. SGS Colombia S.A. es un proveedor global de servicios de verificación técnica, inspección, ensayos y conformidad de avalúos, inculcando confianza a los clientes. Aseguramos que la calidad y el desarrollo de sus productos o instalaciones cumplen con los requerimientos aplicables, ya sean regulatorios, voluntarios o especificaciones del cliente. La meta es ayudar a mejorar la integridad, calidad y la eficiencia de los equipos, asegurar las condiciones de seguridad y bienestar de los trabajadores y a minimizar el impacto de las actividades industriales. Estos servicios son aplicados en ingeniería, proyectos de construcción, mejoramiento en las actividades de mantenimiento. Los empleados de sector de Servicios industriales son los mejores calificados y reconocidos expertos en la industria. Tenemos décadas de experiencia, nuestro trabajo es reconocido por numerosas acreditaciones por organismos internacionales así como especificaciones estándar de nuestros clientes. Nuestra experiencia puede ayudarle a mejorar las condiciones de sus empleados en seguridad y salubridad, y en el impacto ambientar de sus actividades. ESTUDIOS TÉCNICOS S.A. es una compañía de ingenieros fundada en 1964 con el propósito de prestar servicios de ingeniería para buscar, definir y llevar a la práctica soluciones integrales, innovadoras y económicas a los complejos problemas que el desarrollo plantea a los sectores público y privado, dentro y fuera del país. Desde su fundación, ha realizado trabajos de en las líneas de Diseño, Interventoría, Estudios, y Consultoría, Ingeniería Básica y de Detalle, Gerencia de Proyectos y Construcción, Avalúos Industriales e Inspección de Fabricación y Montaje de Equipos en todo el territorio Colombiano, contribuyendo al desarrollo del país. Varios de sus trabajos han sido ejecutados en consorcio con firmas nacionales o en consorcio o con asesoría de firmas extranjeras. Un número importante de proyectos en los que se ha trabajado han sido financiados con créditos de entidades como: Banco Interamericano de Desarrollo BID, Banco Internacional de Reconstrucción y Fomento - BIRF y Programa de las Naciones Unidas para el Desarrollo PNUD. SGS ETSA actualmente desarrolla varios contratos macro con Ecopetrol S.A. que le abren las puertas y lo posicionan como una empresa líder en el mercado. Con la necesidad de expansión y de prestar un servicio que satisfágala las expectativas de sus clientes SGS ETSA requiere la implementación de un sistema integrado de gestión, que le permita obtener un óptimo desempeño en su actividad comercial, trayendo consigo beneficios económicos, la optimización de sus recursos por medio de la eficacia y eficiencia en el ejercicio de su labor. Con la ampliación del mercado se ha hecho necesario implementar metodologías que permitan a las organizaciones ser más competitivas, no solamente a nivel nacional sino internacional, siendo de vital importancia la satisfacción del cliente en todos sus aspectos. Con la implementación de sistemas de calidad basados en la Norma ISO 9001 versión 2001 las empresas dan un paso adelante en el desarrollo de sistemas administrativos basados en la Gestión Integral, lo cual redunda a mediano y largo plazo en su supervivencia y crecimiento. SGS ETSA consciente de esa necesidad se ha encaminado a la consecución de la calidad de sus productos para este caso puntual se decide implementar un sistema integral que se adapte al diseño para cada proyecto de hidrocarburos; es por esta razón que se decide realizar el diseño del sistema de gestión integral ISO 9001 ISO 27000, tomando como ejemplo y campo de investigación el Contrato No. 0010649 cuyo objeto es “Diseños civiles, eléctricos y de tubería para las facilidades de la campaña de perforación de la vicepresidencia de exploración y producción vigencia 2013”.
Keywords: Calidad; Sistemas integrados de gestión; Seguridad Industrial; Quality; Industrial Security; Integrated Management Systems